The pharmacist's liability in the tort of negligence and product liability law in Ireland - Byrne, Gerald (Trinity College (Dublin, Ireland). School of Law, 2012)
This thesis encompasses historical and legal comparative enquiries into the pharmacy and the law affecting its practitioners. The major research themes are the possible application of the professional negligence standard to pharmacists, emerging new areas of potential liability, as pharmacists expand their role and related issues regarding causation and proof, where there is evidence of a new judicial willingness to modify traditional rules.
Keywords: Law, Ph.D.; Ph.D. Trinity College Dublin